Deep Vein Thrombosis: How do I Manage in Daily Practice - Sidhi Laksono (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2020)
Deep vein thrombosis (DVT) is part of venous thromboembolism disease dan the incidence increases sharply with age. In European countries, DVT incidence is 70-140 cases/100,000 person-year. Patient with DVT, short-term mortality rates were 2-5% and more frequent in proximal than distal DVT. DVT is a common condition for complication such as post phlebitic syndrome, pulmonary embolism and death. An algorithm strategy combining pre-test probability, D-dimer testing and compressible Doppler ultrasound imaging can be applied for suspected lower extremity DVT. Patients with low pre-test probability and a negative D-dimer test result can be excluded from diagnosis of DVT without the need for Doppler ultrasound imaging. Primary treatment of DVT is anticoagulation therapy, intervention using thrombolysis and vena cava filters are for special conditions. The duration of anticoagulation therapy depends on the risk factors.